Risk factors and preventive strategies for post-traumatic stress disorder in neonatal intensive care unit - Di Chiara, Maria; Laccetta, Gianluigi; Gangi, Sara; De Santis, Benedetta; Spiriti, Caterina; Attenni, Martina; Bertolaso, Laura; Boscarino, Giovanni; De Nardo, Maria Chiara; Ciambra, Gianluca; Parisi, Pasquale; Terrin, Gianluca (Frontiers in Psychology, 2022)
Background: Preterm birth and the admission in neonatal intensive care unit (NICU) could induce a post-traumatic stress disorder (PTSD). PTSD is associated with parental mental health difficulties and with changes in caregiving quality such as increased intrusiveness, reduced sensitivity, and increased attachment insecurity for the child. Aims: we aimed to study the main risk factors, in the early life of newborn, and preventive measures for PTSD in parents of neonates hospitalized in the NICU. Methods: We included parents of preterm newborns, consecutively admitted to the NICU of University La Sapienza of Rome. The presence of PTSD following preterm birth and NICU admission was assessed by means of the Clinician-administered PTSD scale (CAPS) at the enrollment and at 28-30 days following NICU admission or at the moment of discharge. We also evaluated Family Environment Scale, Parental Stressor Scale, Spielberger State—Trait Anxiety Inventory and Beck Depression Inventory Second Edition. Results: We found, in a multivariate analysis, that GA of newborns admitted in NICU significantly (β 2.678; p=0.040) influences the occurrence of PTSD. We found that cases showed a significantly (β 2.443; p=0.020) more pathological PSS:NICU sights and sounds scores compared to controls. The early KC significantly (β -2.619; p=0.015) reduces the occurrence of PTSD. Conclusion: PTSD in parents of preterm newborns is a pathological condition that should be properly managed, in the very first days after birth. The NICU environment represents a main risk factor of PTSD, whereas KC has been demonstrated to have a protective role in the occurrence of PTSD.